2014
DOI: 10.1177/1687814020926309
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anchorage performance of the switchboard cabinet under seismic loading condition

Abstract: In this study, the seismic response of the anchorage used for switchboard cabinets at a power plant was presented based on the results of an experiment and numerical simulations. In the experimental study, shaking table tests were performed to investigate the overall structural behavior of switchboard cabinets. The finite element modeling was conducted using the ABAQUS program, and in order to validate the proposed finite element model, the natural frequency, stress, and displacement were compared with the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…To perform an exhaustive assessment, vibration modes, fundamental periods/frequencies, and damping ratios evolution should be associated with the damage process evolution, considering undamaged, partially, and fully damaged conditions (or at least all the DSs reached during the tests Several testing methods were used in the literature to identify the dynamic characteristics of NEs. Random noise excitation tests (Cosenza et al, 2015;Di Sarno et al, 2019;Fiorino et al, 2019;Jun et al, 2020;Lu et al, 2018;Luo et al, 2021;Petrone et al, 2017;Qi et al, 2021) and sine sweep tests (Kim & Shin, 2021;Lee & Jung, 2020;Lin et al, 2014;Son et al, 2020) are among the most used ones, and no studies, to the knowledge of the authors, identified the differences among the different methods in terms of dynamic properties assessment results or supplied motivations for preferring the use of one specific method. Even though the methods defined within the relevant protocols or in the literature can be considered to be relatively reliable, the absence of a preferred method and the lack of standardized definitions might condition the robustness of the estimations, especially considering comparison purposes.…”
Section: Dynamic Identification Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…To perform an exhaustive assessment, vibration modes, fundamental periods/frequencies, and damping ratios evolution should be associated with the damage process evolution, considering undamaged, partially, and fully damaged conditions (or at least all the DSs reached during the tests Several testing methods were used in the literature to identify the dynamic characteristics of NEs. Random noise excitation tests (Cosenza et al, 2015;Di Sarno et al, 2019;Fiorino et al, 2019;Jun et al, 2020;Lu et al, 2018;Luo et al, 2021;Petrone et al, 2017;Qi et al, 2021) and sine sweep tests (Kim & Shin, 2021;Lee & Jung, 2020;Lin et al, 2014;Son et al, 2020) are among the most used ones, and no studies, to the knowledge of the authors, identified the differences among the different methods in terms of dynamic properties assessment results or supplied motivations for preferring the use of one specific method. Even though the methods defined within the relevant protocols or in the literature can be considered to be relatively reliable, the absence of a preferred method and the lack of standardized definitions might condition the robustness of the estimations, especially considering comparison purposes.…”
Section: Dynamic Identification Testsmentioning
confidence: 99%
“…Dynamic testing also allows the assessment of the dynamic properties of the elements (e.g., dynamic identification). Shake table testing represents state‐of‐the‐art dynamic testing (Bianchi et al., 2021; Filiatrault et al., 2004; Ghith et al., 2019; Jun et al., 2020; Kim & Shin, 2021; Lee & Jung, 2020; Luo et al., 2021; Magliulo et al., 2014; Qi et al., 2021; Tian et al., 2015; T. Zhou et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Before analyzing the seismic motion load characteristics of the anchorage, the natural frequency of the target structure was measured through a shaking table test with reference to the previous study 14 that evaluated the performance of the anchorage of the electric cabinet during the earthquake.…”
Section: Introductionmentioning
confidence: 99%